Triadic Love Structure in Zaynab by Muhammad Husain Haykal - Devira Kumala Dewi; Abdul Muntaqim Al Anshory (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the representation of love in Zaynab by Muhammad Husain Haykal through the triadic structure of love. The research departs from the assumption that love in the novel is not merely portrayed as romantic attachment but as a relational configuration shaped by personal emotion and socio-cultural constraints. Using a qualitative descriptive method with textual analysis, this study identifies and categorizes narrative evidence into three dimensions: intimacy, passion, and commitment. The findings reveal that intimacy is constructed through emotional openness, secrecy, and psychological attachment, while passion appears in intense affective reactions and longing. However, commitment is predominantly formed through familial authority and social obligation rather than mutual emotional choice. This imbalance among the three dimensions prevents the realization of a harmonious love structure and results in psychological conflict and narrative tragedy. The study demonstrates that love in Zaynab by Muhammad Husain Haykal operates as a complex relational structure in which cultural norms significantly influence emotional experience. By analyzing the interaction among intimacy, passion, and commitment, this research highlights how socio-cultural pressures reshape personal affection and contribute to the tragic development of the protagonist.